Conservative Bridge Preparation By Using Natural Tooth As A Pontic With Ribbond Fiber: A Case Report At IIDH Islamabad - Azhar, Muhammad Daniyal; Ghani, Momina; Awan, Tahir; Rizwan, Zarnab; Sajid, Khadija; Haq, Abdul (Journal of Rawalpindi Medical College, 2023)
Summary: Traumatic damage to anterior teeth is a common form of dental injury, particularly in younger people. The abutment teeth only need to be slightly prepared for the conservative bridge preparation, as the name suggests. The final prosthesis can be fixed to the adjacent natural teeth in no time. This case reports a chair-side conservative and esthetic restoration in a 19-year-old girl who came with grade 3 mobility in her upper left central incisor by using her natural tooth as a pontic with ribbond fibre. Keywords: Conservative, Dental trauma, Ribbond fiber